KEADILAN ORGANISASIONAL DAN KEPUASAN KERJA: PENGUJIAN KETERKAITAN EQUITY THEORY DENGAN WORK OUTCOMES - Wiyono Wiyono (Benefit: Jurnal Manajemen dan Bisnis, 2004)
The purpose of this study is to examine relationship between equity theory and work outcomes ineducational staff’s context. To operationalize these constructs, equity theory was measured by threedimensions of organizational justice, namely procedural, interactional and distributive justice, whileorganizational outcome was measured by job satisfaction. The result of study shows that all dimensionsof organizational justice have significant effect to job satisfaction. Conclusion about relationship betweenequity theory and work outcomes and recommendations for future research also discussed.